Hak Cipta atas Karya di Internet: Pengaturan dan Upaya Perlindungannya - Budi Agus Riswandi (Jurnal Hukum IUS QUIA IUSTUM, 2007)
The born of digital image creation in the Internet stipulates legal impacts. One of the impacts  is  copy rights law. The copy rights law should be  able to respond the digital image phenomena in the internet. The Indonesian Copy rights law  is regulated on the Act No. 19 /2002.  In fact, this Act has regulated digital creations in  the internet. This indicates that the Act provides protection to the creations. Is it true ?